Characterizing Concealed Fault Systems by Integrating Field Data Mapping and Laboratory Experiments: A Case Study of the Huawa Area in East China - Hu, Huiting; Hu, Shuang; Zhang, Rui; Fu, Xiaofei; Ren, Chongyu; Liu, Qidong; Yu, Wenquan; Yang, Yuchen (Frontiers in Earth Science, 2021)
Concealed faults can be important for understanding the regional structural geology and the subsurface fluid distribution. However, such faults are usually difficult to identify and characterize because of their small size and complex mechanism. To address this issue, we present an integrated approach of three-dimensional seismic data mapping and physical modeling experiments to examine the geometrical and kinematic characteristics of concealed faults and their relationship with the main faults in the Huawa area, east China. Three series of experiments were designed to characterize the differences in the scale of concealed faults and main faults, which also allowed us to examine how the concealed faults grow with the main faults in the area. Through this integrated study, we have demonstrated that: i) NE-SW-striking concealed faults are below the resolution of the available seismic datasets and not easily recognized in seismic sections and that most of them grew later than the E-W-striking main faults, with some of them having grown at the same time; ii) pre-existing faults, rather than asymmetry of the basin structure, affect the faults that develop during subsequent episodes of extension; iii) E-W-striking pre-existing faults under a NW-SE stress direction of extension are most likely the formation mechanism of concealed faults.